2011
DOI: 10.2134/agronj2010.0511
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Photoperiod Effects on Vicia faba Phenology Simulated by CROPGRO‐Fababean

Abstract: Models may be useful tools to design effi cient crop management practices provided they are able to accurately simulate the eff ect of weather variables on crop performance. Th e objective of this work was to accurately simulate the eff ects of temperature and day length on the rate of vegetative node expression, time to fl owering, time to fi rst pod, and time to physiological maturity of faba bean (Vicia faba L.) using the CROPGRO-Fababean model. Field experiments with multiple sowing dates were conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Lizarazo et al (2015) calculated the GDD in faba bean grown under Nordic conditions using 5°C as base temperature, which is used for several crops. Confalone et al (2011) found that the base temperature varied across phenological phases, with a base temperature from flowering to maturity likely >0°C. To our knowledge, consensus about base temperatures to be used for faba bean is lacking and, particularly, for the period of seed development and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Lizarazo et al (2015) calculated the GDD in faba bean grown under Nordic conditions using 5°C as base temperature, which is used for several crops. Confalone et al (2011) found that the base temperature varied across phenological phases, with a base temperature from flowering to maturity likely >0°C. To our knowledge, consensus about base temperatures to be used for faba bean is lacking and, particularly, for the period of seed development and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Calculations and Statistical Analyses. For both crops, growing degree days (GDD) were accumulated from the date of emergence (time zero) using a base temperature (T b ) of 2 C; this value was assumed to be valid for both crops, being within the range of previous estimates for chickpea (Confalone et al 2011;Dumur et al 1990) and faba bean (Singh 1991;Summerfield et al 1990). GDD for each day were calculated from the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…The duration and dry matter accumulation of faba bean plants before flowering greatly depended on temperature and thermal units and soil moisture (Darwish et al, 2016) in addition to photoperiod (Confalone, et al, 2011). However, (Bishop et al, 2016 andQuarshie et al, 2021) concluded the importance of thermal units in the growth, development and seed yield of faba bean genotypes.…”
Section: Mean Effects Of Environmentsmentioning
confidence: 99%